Mechanical and thermal properties of graphene oxide filled epoxy nanocomposites - Noorhafanita Norhakim,; Sahrim Hj. Ahmad,; Chin, Hua Chia; Nay, Ming Huang (Universiti Kebangsaan Malaysia, 2014)
In this study, graphene oxide (GO) filled epoxy nanocomposites were prepared using hot pressed method. The GO was produced using modified Hummers’ method. The produced GO at different compositions (0.1, 0.3 and 0.5 wt%) were mixed with epoxy before the addition of hardener using ultra-sonication. The produced epoxy nanocomposites were characterized in terms of mechanical and thermal properties. The mechanical properties of the nanocomposites were significantly enhanced by the addition of GO. About 50% of increment in the flexural strength of the composite sample filled with 0.3 wt% of GO as compared to the neat epoxy sample. However, only slight improvement in the impact strength of the composite were obtained by adding 0.1 wt% of GO.